A95 INFLAMMATORY PROTEASES DRIVE A MIGRATORY INTESTINAL EPITHELIAL PHENOTYPE THROUGH THE GENERATION OF BIOACTIVE PEPTIDE FRAGMENTS OF E-CADHERIN. (1st March 2018) - Gordon, M; Chauvin, A; Boisvert, F; MacNaughton, W
Abstract: Background: The inflammatory microenvironment in the gut contains a variety of proteases which are known to be increased in patient samples in both IBD and CRC. How these proteases and their proteolytic peptide products contribute to wound resolution has been poorly elucidated. A cellular switch from a "barrier" to a "migration/repair" phenotype is required for healing in IBD, but is also a hallmark of tumorigenesis. Proteolytic degradation of epithelial E-cadherin (Ecad) is necessary for this process, we have been studying the biological activity small peptide fragments of Ecad generated by neutrophil elastase, an inflammatory protease elevated in IBD. We have been studying the ability of proteases to induce a switch in the colonic epithelium from a barrier to a repair phenotype (epithelial to mesenchymal transition [EMT]) characterized by increased migration and disrupted homeostasis. Aims: To test the hypothesis that inflammatory proteases process Ecad into small bioactive peptides that contribute to wound resolution. Methods: Recombinant Ecad was incubated with neutrophil elastase (NE) in vitro to produce NE-dependent Ecad peptides. Six of these peptides shared partial homology with Ecad peptides identified by mass spectrometry in IBD patient samples, and were chosen for further characterization. Peptides were synthesized and assayed for their ability to alter wound healing capacity, proliferation, cell spreading, and cytotoxicity in Caco-2 cells using the IncuCyte™ live-cell imaging system for 48 hours following exposure to 1, 10, and 100 mg/mL concentrations of peptides. All analysis was done using the IncuCyte™ ZOOM platform in conjunction with ImageJ software. Results: We have identified 6 Ecad peptides produced by neutrophil elastase activity that appear to be increased in IBD patient tissue. We have characterized these peptides to have novel biological roles in altering wound resolution and proliferation rates, with 3 peptides showing significantly increased wound healing capacity at at least one concentration. These 3 peptides (KAADTDPTAPPYD, NRNTGVISVV, and LPPEDDTRDNV) showed improved wound closures of approximately 7–10% under serum free conditions and 5–10% under full serum conditions compared to controls. Preliminary data also suggests that these peptides appear to have a positive effect on proliferation rates, and appear to alter cellular morphology of cells to that of a more flattened cell type, typical of repair programming of cells to cover a denuded area. Conclusions: Our data reveal a novel role for proteolytic processing of Ecad under inflammatory conditions, producing bioactive peptides that drive a wound-healing phenotype in epithelial cells in response to damage. Funding Agencies: CIHRUniversity of Calgary Faculty Seed Grants